The relationship between glycine levels in collagen in the anterior rectus sheath tissue and the onset of indirect inguinal hernia: A cross-sectional study. (January 2022) - Fajar, Amir; Warsinggih,; Syarifuddin, Erwin; Hendarto, Joko; Labeda, Ibrahim; Lusikooy, Ronald Erasio; Mappincara,; Dani, Muhammad Iwan; Sampetoding, Samuel; Kusuma, Muhammad Ihwan; Uwuratuw, Julianus Aboyaman; Faruk, Muhammad
Abstract: Introduction: An inguinal hernia is a protrusion of abdominal-cavity contents through the inguinal canal. Protection against an inguinal hernia depends on the integrity of fascial tissue, which is maintained by collagen. Collagen is a structural protein consisting of amino acids, the most common of which is glycine. This study aimed to determine the relationship between glycine and the appearance of lateral inguinal hernias. To this end, the researchers examined the profile of collagen and glycine levels in the tissue of the sheath of the rectus femoris in patients with lateral inguinal hernia (indirect inguinal hernia). Methods: The study used a cross-sectional design to determine glycine levels in rectus anterior sheath tissue in patients with indirect inguinal hernia. Examination of collagen glycine levels was conducted using the ELISA (Enzyme-Linked immunosorbent assay) method. Data were analyzed using the Statistical Package for the Social Science (SPSS) program. An ANOVA test, Pearson's correlation test, and Spearman's correlation test were also performed. A p-value <0.05 was said to be significant. Results: Across 72 samples, the mean body mass index (BMI) was 22.5 kg/m2 and, the mean clinical onset was 28.02 months. Correlation tests showed a correlation between glycine levels and clinical onset (p = 0.026). The ANOVA test showed a difference between glycine levels with age group (p = 0.025) and BMI (p = 0.015). The correlation between glycine levels and clinical-grade (p = 0.416) was not statistically significant. Conclusion: There is a significant relationship between glycine levels and age, BMI, and clinical onset of indirect inguinal hernia. Highlights: The stability of the abdominal wall depends on the integrity of muscle and fascial tissue. Collagen is a structural protein that helps tissues maintain their mechanical characteristics, structure, and shape. The collagen structure contains amino acids such as glycine, proline, hydroxyproline, alanine, and hydroxylysine. The high glycine content of collagen is vital to promoting collagen turnover, as its deficiency reduces collagen turnover. There is a relationship between glycine levels and age, body mass index, and clinical onset of indirect inguinal hernia.